An In-Depth Examination of Reasons for Autopsy Acceptance and Refusal in Northern Tanzania - Blum, Lauren S. (Am J Trop Med Hyg, 2020)
Uncertainty about the causes of death (COD) in low- and middle-income countries (LMICs) has been recognized as a constraint to global health and development. Although complete diagnostic autopsy (CDA) is the best way to assess COD, it is uncommon in LMICs because of low investment priority and assumptions about poor acceptability. Social science research was conducted from May 2016 through July 2017 to examine issues related to acceptability of CDAs in northern Tanzania where autopsy was being offered in two referral hospitals to assess COD associated with febrile illness. Initial formative research entailed 29 key informant interviews, seven observations of burial practices, and four group discussions. In-depth interviews were conducted with families of deceased, including nine families that accepted and 11 families that refused CDA. The formative research identified concepts related to death, understandings of CDA, and cultural practices and psychosocial considerations associated with death that informed the authorization process. Most families who accepted CDA cited the desire to get clarity regarding the COD as a primary reason for acceptance. An unexpected finding was that CDA is perceived as a means to determine witchcraft involvement, a common explanation for COD and a common reason for postmortem acceptance. Death resulting from chronic illness or conditions presumed to have a clinical diagnosis were reasons for CDA to be viewed as unnecessary. The timing, way families were approached, and content of information shared during authorization influenced acceptance and refusal of CDA. Findings show that CDAs can be acceptable in settings where traditional disease models prevail.